2002
DOI: 10.1046/j.1365-2710.2002.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with use of recombinant activated factor VII

Abstract: Recombinant activated factor VII (rFVIIa) has recently been introduced for improving haemostasis in haemophiliac patients developing alloantibodies (inhibitors) to factor VIII (FVIII) or factor IX (FIX). We describe the successful management of haemorrhagia with rFVIIa in five different situations: an episode of surgical bleeding in a patient with haemophilia A and non-surgical haemorrhages in four patients with haemophilia A, acquired haemophilia, congenital severe FV defect and pseudo-acquired haemophilia, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…The authors of that report concluded that rFVIIa did not appear to be immediately responsible for the thrombosis, noting that after administration of rFVIIa, the ECMO circuit was functioning well and only after APCC was given did the thrombosis occur. The association of APCC with thrombotic events has been noted in the past (17).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that report concluded that rFVIIa did not appear to be immediately responsible for the thrombosis, noting that after administration of rFVIIa, the ECMO circuit was functioning well and only after APCC was given did the thrombosis occur. The association of APCC with thrombotic events has been noted in the past (17).…”
Section: Discussionmentioning
confidence: 99%
“…The dose regimen used in these two patients was 100 μ g kg −1 every 2 h for three doses day −1 ; the duration of treatment varied according to the severity of the bleeding. In addition, another patient with inhibitor to FV was treated with rFVIIa for a severe knee joint bleed [3]. rFVIIa 80 μ g kg −1 was given every 3 h for three doses on the first day, every 4 h for three doses on the second day, and every 4 h for two doses on the third day.…”
Section: Discussionmentioning
confidence: 99%
“…Only English language literature was considered. Fifty articles were subsequently identified [10–57]. Underlying coagulopathy and/or the results of rFVIIa treatment in congenital haemophilia patients with inhibitors could be ascertained in only 46 of the 50 articles identified.…”
Section: Methodsmentioning
confidence: 99%